PENGUATAN KELEMBAGAAN BUMDES - Sriyoto 01; Rihan Ifebri M.Si (Lembaga Penelitian dan Pengabdian Pada Masyarakat Universitas Tamansiswa Padang, 2023)
BUMDes institutional strengthening is important in the development of Village BUMDes, The idea of ??BUMDes in Lokasi Baru Village is to synergize with the community in terms of meeting community needs, joint institutional management and increasing economic potential. The identification of BUMDes problems carried out includes increasing the capacity of human resources in governance, development planning and priorities and marketing strategies, creativity and innovation so that they can collaborate with other partners.The solutions offered in this activity are training and mentoring to increase partners' knowledge and skills in strengthening BumDes institutions, studying BumDes business concepts and planning through making proposals or business planning modules. The output of this activity is the formation of collaboration between BUMDes managers and the Department of Agribusiness, University of Bengkulu, identification of problems, and determining the description of BUMDes development planning for lokasi Baru Village